Wages, rents, unemployment, and the quality of life - Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2012)
Combining a spatial equilibrium model with a matching unemployment model, this paper analyzes the regional quality of life when wages, rents, and unemployment risk compensate for local amenities and disamenities. In particular, the paper shows for quasi-linear utility that the effects of any amenity on wages and unemployment rates are of opposite sign. Additionally, the wage rate and the labor market tightness increase and the unemployment ratio decreases in reaction to an increase in the level of an amenity if the amenity is marginally more beneficial to producers than to consumers per unit of land. Based on the model, quality of life of average mobile workers in West German counties is estimated.
Keywords: R12; R13; R14; H73; J61; J64; 330; quality of life; unemployment; job search; matching; mobility